A java API interface for the integration of DTV services in embedded multimedia devices - Vidakovic, M.; Maruna, T.; Teslic, N.; Mihic, V. (IEEE transactions on consumer electronics, 2012)
Most of the modern DTV sets and set top boxes are embedded Linux devices. Apart from playing broadcast transport streams, some of these devices offer network connectivity and various applications. The development of software for these devices is not unified, so there is no compatibility between applications developed by different vendors. On the other hand, there are embedded systems developed on top of the embedded Linux kernel which offer network connectivity and a large number of applications that are available for download. Most of the applications developed for these platforms are developed in the Java programming language. However, those platforms do not support DTV services. This paper presents a proposal for the integration of DTV services into embedded systems which support the Java programming language. The proposed solution offers complete DTV functionality, along with the operation of regular applications. The proposal includes two API specifications: the Java API that is used to access DTV content from Java applications, and the DTV Middleware API that is used to connect the native code to the Java API.